2019
DOI: 10.3390/app10010001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functional Group Density of Anion Exchange Resins on Removal of p-Toluene Sulfonic Acid from Aqueous Solution

Abstract: Adsorption using anion exchange resins is an efficient method for the removal of aromatic sulfonic acids (ASAs) from industrial wastewater. In this study, a series of weak-base anion exchangers (SD1–SD5) were synthesized to investigate the effect of functional group density of resins on the adsorption of ASAs from wastewater containing competitive inorganic anions. p-Toluene sulfonic acid (PTSA) was selected as a target pollutant, and Na2SO4 was chosen as the competitive inorganic salt because of its widesprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Acidity of the solution is one of the most important factors affecting the adsorbent capacity in wastewater treatment. Adsorption efficiency depends on the pH of the solution because changes in pH lead to changes in the degree of melting properties (Kumar et al 2019). Therefore, pH is mentioned as an important parameter in color adsorption.…”
Section: Effect Of Phmentioning
confidence: 99%
“…Acidity of the solution is one of the most important factors affecting the adsorbent capacity in wastewater treatment. Adsorption efficiency depends on the pH of the solution because changes in pH lead to changes in the degree of melting properties (Kumar et al 2019). Therefore, pH is mentioned as an important parameter in color adsorption.…”
Section: Effect Of Phmentioning
confidence: 99%
“…Aung et al [5] reported the removal of Cu(II) from aqueous solutions using amine-doped polyacrylonitrile fibers. Sun et al [6] investigated the effect of the functional group density of anion-exchange resins on the removal of p-toluene sulfonic acid from an aqueous solution. Hwang et al [7] reported how arsenic leaches from different soil and sediment types and responds to hydrologic conditions to identify areas susceptible to arsenic contamination.…”
mentioning
confidence: 99%